Comparison of high‐resolution synchrotron‐radiation‐based phase‐contrast imaging and absorption‐contrast imaging for evaluating microstructure of vascular networks in rat brain: from 2D to 3D views. (11th September 2019) - Li, Hong-Lei; Ding, Hui; Yin, Xian-Zhen; Chen, Zhuo-Hui; Tang, Bin; Sun, Jing-Yan; Hu, Xin-Hang; Lv, Xinyi; Kang, Shun-Tong; Fan, Yi-Shu; Wu, Tong; Zhao, Song-Feng; et al.
Abstract : The synchrotron‐radiation‐based phase‐contrast imaging method is a more effective tool than absorption‐contrast imaging for systematic visualization of cerebral microvasculature, which holds considerable promise for wider application in life sciences, including 3D micro‐imaging in experimental models of neurodevelopmental and vascular disorders. Abstract : Conventional imaging methods such as magnetic resonance imaging, computed tomography and digital subtraction angiography have limited temporospatial resolutions and shortcomings like invasive angiography, potential allergy to contrast agents, and image deformation, that restrict their application in high‐resolution visualization of the structure of microvessels. In this study, through comparing synchrotron radiation (SR) absorption‐contrast imaging to absorption phase‐contrast imaging, it was found that SR‐based phase‐contrast imaging could provide more detailed ultra‐high‐pixel images of microvascular networks than absorption phase‐contrast imaging. Simultaneously, SR‐based phase‐contrast imaging was used to perform high‐quality, multi‐dimensional and multi‐scale imaging of rat brain angioarchitecture. With the aid of image post‐processing, high‐pixel‐size two‐dimensional virtual slices can be obtained without sectioning. The distribution of blood supply is in accordance with the results of traditional tissue staining. Three‐dimensional anatomical maps of cerebral angioarchitecture can also be acquired. Functional partitions of regions of interest are reproduced in the reconstructed rat cerebral vascular networks. Imaging analysis of the same sample can also be displayed simultaneously in two‐ and three‐dimensional views, which provides abundant anatomical information together with parenchyma and vessels. In conclusion, SR‐based phase‐contrast imaging holds great promise for visualizing microstructure of microvascular networks in two‐ and three‐dimensional perspectives during the development of neurovascular diseases.